2017
DOI: 10.1002/jso.24614
|View full text |Cite
|
Sign up to set email alerts
|

UCH‐L1‐containing exosomes mediate chemotherapeutic resistance transfer in breast cancer

Abstract: Our study demonstrated that UCH-L1-containing exosomes can transfer chemoresistance to recipient cells and these exosomes may be useful as non-invasive diagnostic biomarkers for detection of chemoresitance in breast cancer patients, achieving more effective and individualized chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 29 publications
3
86
0
Order By: Relevance
“…showed that the delivery of P‐gp through exosomes could impart drug resistance to MCF‐7 breast cancer cells . This result indicated that the adriamycin‐resistant cells secreting exosomes can not only carry ubiquitin carboxyl terminal hydrolase‐L1 to recipient cells, but can also enhance the expression of P‐gp proteins through the MAPK/ERK signaling pathway . The expression level of exosomal glutathione S‐transferase P1 (GSTP1) was also upregulated in adriamycin‐resistant cells.…”
Section: Chemotherapymentioning
confidence: 97%
See 1 more Smart Citation
“…showed that the delivery of P‐gp through exosomes could impart drug resistance to MCF‐7 breast cancer cells . This result indicated that the adriamycin‐resistant cells secreting exosomes can not only carry ubiquitin carboxyl terminal hydrolase‐L1 to recipient cells, but can also enhance the expression of P‐gp proteins through the MAPK/ERK signaling pathway . The expression level of exosomal glutathione S‐transferase P1 (GSTP1) was also upregulated in adriamycin‐resistant cells.…”
Section: Chemotherapymentioning
confidence: 97%
“…34 This result indicated that the adriamycin-resistant cells secreting exosomes can not only carry ubiquitin carboxyl terminal hydrolase-L1 to recipient cells, but can also enhance the expression of P-gp proteins through the MAPK/ERK signaling pathway. 35 The expression level of exosomal glutathione S-transferase P1 (GSTP1) was also upregulated in adriamycin-resistant cells. Glutathione S-transferase P1 belongs to the family of phase II metabolic enzymes, and has been reported to detoxify several anticancer drugs by conjugating them with glutathione.…”
Section: Breast Cancermentioning
confidence: 99%
“…Secondly, there is a large amount of drug and chemoresistance proteins in the exosome. GSTP1, TGF-β1, TPRC5, and UCH-L1 are examples [97][98][99][100]. Finally, proteins that induce metastasis present highly in exosomes.…”
Section: Cell Ultracentrifugementioning
confidence: 99%
“…Drug and chemotherapy resistance [97] TGF-β1 Drug resistance [98] TPRC5 Chemotherapy resistance [99] UCH-L1 Chemotherapy resistance [100] Nephronectin Induce tumor mestasis [101] Caveolin-1 Enriched in metastasized cancer cell [36] Periostin Enriched in metastasized cancer cell [102] Myoferlin Enriched in metastasized cancer cell [31] Lung Cancer Mucin 5AC, B Lung cancer relapse and metastasis [103,104] Desmoglein-2 overspressed in non small cell lung cancer and induce cell growth [105] EGFR Oncogene in lung cancer [106,111,113,114] LRG1 Induce angiogenesis [108] Tim-3 Induce anti-tumor immune response [110] NY-SEO-1 Overexpressed in lung cancer [111] [111] EpCam Overexpressed in lung cancer [111] SGRN Overexpressed in lung cancer [112] TPM3 Overexpressed in lung cancer [112] THBS1 Overexpressed in lung cancer [112] HUWE1 Overexpressed in lung cancer [112] MUC 1 Overexpressed in lung cancer [112] Colon Cancer…”
Section: Gstp1mentioning
confidence: 99%
“…11 These extracellular vesicles (EVs) have been reported to facilitate the crosstalk between cells by transporting a unique composition of proteins, lipids and RNA species 12 contributing to the regulation of the tumour microenvironment (TME). 13 Exosomes isolated from docetaxel-resistant MCF-7 cells, for instance, have upregulated levels of proteins involved in multidrug-resistance [14][15][16] and can induce resistance in MCF-7 drug-sensitive cells. 17 Moreover, TDE are directly involved in anti-neoplastic drugs' elimination from cancer cells.…”
Section: Introductionmentioning
confidence: 99%